2021
DOI: 10.48550/arxiv.2107.09929
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Magnetic field tuning of the spin dynamics in the magnetic topological insulators (MnBi$_{2}$Te$_{4}$)(Bi$_{2}$Te$_{3}$)$_{n}$

A. Alfonsov,
K. Mehlawat,
A. Zeugner
et al.

Abstract: We report a high frequency/high magnetic field electron spin resonance (HF-ESR) spectroscopy study in the sub-THz frequency domain of the two representatives of the family of magnetic topological insulators (MnBi2Te4)(Bi2Te3)n with n = 0 and 1. The HF-ESR measurements in the magnetically ordered state at a low temperature of T = 4 K combined with the calculations of the resonance modes showed that the spin dynamics in MnBi4Te7 is typical for an anisotropic easy-axis type ferromagnet whereas MnBi2Te4 demonstrat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
(59 reference statements)
1
0
0
Order By: Relevance
“…While the early synchrotron ARPES studies reported 7,12,14 that the DP gap in MnBi 2 Te 4 persists well above the Néel temperature, recent laser-ARPES data show about 40% reduction of the DP gap (from 65 to 40 meV) upon heating from below T N up to 35 K 71 . An incomplete closing of the gap seems to be consistent with strong short range order effects that persist in MnBi 2 Te 4 up to about 50-60 K, as observed by electron spin resonance, ferromagnetic resonance, and antiferromagnetic resonance experiments 7,72,73 . The measured magnetization data 52 , revealing that MnBi 2 Te 4 is not in the paramagnetic limit even at T ≈ 50 K, confirm this observation.…”
Section: Discussionsupporting
confidence: 71%
“…While the early synchrotron ARPES studies reported 7,12,14 that the DP gap in MnBi 2 Te 4 persists well above the Néel temperature, recent laser-ARPES data show about 40% reduction of the DP gap (from 65 to 40 meV) upon heating from below T N up to 35 K 71 . An incomplete closing of the gap seems to be consistent with strong short range order effects that persist in MnBi 2 Te 4 up to about 50-60 K, as observed by electron spin resonance, ferromagnetic resonance, and antiferromagnetic resonance experiments 7,72,73 . The measured magnetization data 52 , revealing that MnBi 2 Te 4 is not in the paramagnetic limit even at T ≈ 50 K, confirm this observation.…”
Section: Discussionsupporting
confidence: 71%